Determinants of European bank risk during financial crisis - Wiem Ben Jabra; Zouheir Mighri; Faysal Mansouri (Cogent Economics & Finance, 2017)
This paper examines the determinants of European bank risk-taking during major financial crisis. Using a sample of banks from 26 countries over the period 2005-2015, we examine the nature of the relationship between bank risk, bank characteristics, regulatory, institutional and macroeconomic variables. We use a dynamic panel data modeling structure to capture the potential discrepancies in risk-taking behavior. We subdivide our sample into two sub-samples (East Europe and West Europe countries). We show that macroeconomic and regulatory variables seem to have non-negligible impact on bank risk-taking attitudes. We document that the relationship between bank risk, internal and external factors differs across samples.
Keywords: G15; G21; G25; G28; 330; credit risk; insolvency risk; financial crisis; dynamic panel data; GMM; East Europe; West Europe